Teacher reforms around the world implementations and outcomes - Akiba, Motoko (International perspectives on education and society ;, 2013)
During the past decade, many countries have implemented a large-scale reform to improve teacher quality. These reforms have targeted a range of teacher policies including those on recruitment into teaching, pre-service teacher education, certification, hiring and placement, induction and professional development, teacher evaluation, career structure, and compensation. The current global focus on improving teacher quality provides a unique opportunity to learn from the successes and failures of teacher reforms around the world. Previous books on teacher reforms and policies tended to focus on descriptions of teacher policies and their backgrounds, and we have limited knowledge about how these policies were implemented and how they impacted teachers. This edited book fills this knowledge gap by focusing on implementations and outcomes of teacher reforms. The chapters are based on empirical studies that evaluated the implementations and outcomes of major teacher reforms in the countries from various parts of the world: North and South America, Asia and Oceania, Europe, Middle East and Africa. The concluding chapter discusses the lessons learned from these empirical studies and provides recommendations for policymakers around the world who are attempting to improve teacher quality and student learning through teacher reforms.